2008
DOI: 10.1038/nature06942
|View full text |Cite
|
Sign up to set email alerts
|

Assembly reflects evolution of protein complexes

Abstract: A homomer is formed by self-interacting copies of a protein unit. This is functionally important1,2, as in allostery3-5, and structurally crucial because mis-assembly of homomers is implicated in disease6,7. Homomers are widespread, with 50-70% of proteins with a known quaternary state assembling into such structures8,9. Despite their prevalence, their role in the evolution of cellular machinery10,11 and the potential for their use in the design of new molecular machines12,13, little is known about the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
457
3
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 399 publications
(491 citation statements)
references
References 26 publications
27
457
3
4
Order By: Relevance
“…Supporting evidence for this conclusion is provided by a recent mass-spectroscopy study of the conservation and formation of the quaternary structure of protein homomers. 37 This study confirmed that structure alone is sufficient to infer both the evolutionary and physical path of subunit assembly, an example of ''ontogeny recapitulates phylogeny'' at the cellular level.…”
Section: Limitations Of Spontaneous Assembly From Isolated Proteinssupporting
confidence: 70%
“…Supporting evidence for this conclusion is provided by a recent mass-spectroscopy study of the conservation and formation of the quaternary structure of protein homomers. 37 This study confirmed that structure alone is sufficient to infer both the evolutionary and physical path of subunit assembly, an example of ''ontogeny recapitulates phylogeny'' at the cellular level.…”
Section: Limitations Of Spontaneous Assembly From Isolated Proteinssupporting
confidence: 70%
“…Any favored mechanism must take into account the fact that all four Fabs tested in the present study displayed the propensity to form these complexes. It has been reported that 50 -70% of proteins display some positive level of homodimerization (57), which brings up the possibility that the observations in the current work may reflect a more universal tendency among proteins. The phenomena of "protein breathing" and "folding funnels" (58,59) suggest that proteins can vacillate between a number of different conformations that represent entropically favorable free energy states.…”
Section: Discussionmentioning
confidence: 53%
“…Advances in electrospray ionization (ESI) and matrix-assisted laser desorption/ionization (MALDI) has made mass spectroscopy (MS) a powerful tool to assess the architecture, connectivity, evolution, asymmetry of even large multidomain complexes (Bich and Zenobi, 2009;Levy et al, 2008;Kirshenbaum et al, 2010;Sharon, 2013). No requirement for crystals, low sample need (pmol) and short measurement time (min) allowing high-throughput processing are considered to be the main strengths of MS. As it has been shown recently, nanoflow ESI-MS studies can distinguish coexisting protein populations with different number of bound ligands (nucleotides for ATPases) and determine the rank order of binding affinities and the role of transient asymmetries of higher-order ring systems in the function of chaperonins and transcription activators (Dyachenko et al, 2013;Zhang et al, 2014).…”
Section: F Mass Spectroscopymentioning
confidence: 99%
“…In summary, most dimeric proteins including the signalling ones discussed above have closed (face-to-face) C2 symmetries (Levy et al, 2008). Ligand binding to one subunit can trigger conformational changes of the dimer affecting asymmetrically the binding affinity of the two subunits.…”
Section: Structural Symmetry and Transient Asymmetry Of Signalling Prmentioning
confidence: 99%
See 1 more Smart Citation